Beyond the Classroom: Project-Based Learning As a Catalyst for English Proficiency in Higher Education - Nisa, Baiatun; Arfani, Sri; PURWANINGRUM, PRAPTI WIGATI; MEINAWATI, EUIS (Bina Nusantara University, 2025)
As the demand for 21st-century communication skills grows, English language education must evolve beyond grammar and vocabulary to include digital literacy and collaborative competencies. This study explores the distinctive use of Project-Based Learning (PBL) in a first-semester Basic English course for Communication Science students at a private university in Indonesia. The research examines how PBL enhances student engagement, builds speaking confidence, and fosters real-world language use through digital tools, providing a context-specific approach to foundational English education. A qualitative case study design involving 105 students was employed over a 14-week academic period. Data were gathered through student reflections, structured questionnaires, and multimedia project evaluations, and were analyzed thematically to capture students’ learning experiences and performance outcomes. Findings show that PBL significantly boosted speaking confidence, particularly through tasks such as video production and group projects. These tasks were the most effective in improving language skills and student engagement, distinguishing this study from traditional language instruction. However, challenges such as time management, group accountability, and technical difficulties were noted, particularly among students with limited digital literacy. Positive group dynamics and instructor support were critical in overcoming these obstacles. This study offers insights into the intersection of PBL, digital literacy, and language learning, especially for low-level learners in Communication Science. It emphasizes the importance of inclusive, student-centered learning environments that meet the evolving demands of 21st-century communication.